‘Mind your language’: Investigating the common stereotypes depicted in the characters of an EFL sitcom - Elvina Arapah (Proceedings of AICS - Social Sciences, 2017)
The purpose of the study is to examine and describe the common stereotypes portrayed by the characters in the sitcom ‘Mind Your Language.’ It is a British situation comedy that was aired from 1977 to 1986. The story focuses on the English as a Foreign Language class taught by Mr. Jeremy Brown, who had to deal with a diverse background of foreign students or immigrants. The type of research design is descriptive qualitative. The source of data or the subject of the study is downloaded file of the situation comedy ‘Mind Your Language. The object of the study is the common stereotypes that mark particular cultures in terms of the racial and gender profiling, cultures and groups of individuals as they are shown in the Episode 1 of Season 1 from the Series ‘Mind Your Language.’ The analysis applies semiotics technique by having qualitative interpretation on the scenes from that episode in terms of likeness to a particular culture’s common stereotype. It was discovered that some common stereotypes are identified in terms of racial and gender profiling, cultures and groups of individuals.